Role of Sugars and Phenols in Imparting Resistance in Hibiscus Spp. Against Colletotrichum abelmoschii - Naik, S. T. (Indian Forester, 1995)
The mechainism resistance of Hibiscus cannabinus and H. sabdariffa against Colletotrichum abelmoschii estimating the biochemical constituents such as total sugars, reducing sugars and total phenols have been described in detail.